Judi Online dan Kerentanan Pernikahan: Studi Dampak Terhadap Kehidupan Keluarga di Indonesia - Misnawati Zakfah; Arfandi Sanubari; Imran (Sekolah Tinggi Agama Islam Az-Zain Sampang, 2024)
There are several factors that contribute to the occurrence of online gambling, including economic, environmental, religious, curiosity and the desire to try, as well as perceptions of the chances of winning. This writing uses a qualitative research method, with data collection techniques in the form of library research consisting of books, scientific journals, mass media, the internet, and other references. The results of this study show that the number of divorces due to online gambling has continued to increase over the past five years, from 2020 to 2024. This number increased by 32% in one year and skyrocketed by 142.6%. By mid-2024, the number of divorce cases caused by online gambling had reached 2,000, which caught the attention of the government. In response, several steps have been taken, such as tightening regulations to curb the spread of online gambling, blocking online gambling sites, providing counseling and rehabilitation for those addicted to online gambling, and offering guidance and education for couples, both those preparing for marriage and those already married, about the dangers of online gambling to the harmony of family life